Synthesis of [11C]MK-1064 as a new PET radioligand for imaging of orexin-2 receptor - Gao, Mingzhang; Wang, Min; Zheng, Qi-Huang (Bioorganic & medicinal chemistry letters, 2016)
[Display omitted] The reference standard MK-1064 {5″-chloro-N-((5,6-dimethoxypyridin-2-yl)methyl)-[2,2′:5′,3″-terpyridine]-3′-carboxamide} was synthesized from methyl 2-chloro-5-iodonicotinate and 5-(chloropyridin-3-yl)boronic acid in 4 steps with 33% overall chemical yield. The precursor desmethyl-MK-1064 {5″-chloro-N-((5-hydroxy-6-methoxypyridin-2-yl)methyl)-[2,2′:5′,3″-terpyridine]-3′-carboxamide} for radiolabeling was synthesized from 2-bromopyridin-3-ol and 5″-chloro-[2,2′:5′,3″-terpyridine]-3′-carboxylic acid in 6 steps with 17% overall chemical yield. The target tracer [11C]MK-1064 {5″-chloro-N-((5-[11C]methoxy-6-methoxypyridin-2-yl)methyl)-[2,2′:5′,3″-terpyridine]-3′-carboxamide} was prepared by O-[11C]methylation of its corresponding precursor desmethyl-MK-1064 with [11C]CH3OTf under basic condition and isolated by a simplified solid-phase extraction (SPE) method in 50–60% decay corrected radiochemical yields based on [11C]CO2 at end of bombardment (EOB). The overall synthesis time from EOB was 23min, the radiochemical purity was >99%, and the specific activity at end of synthesis (EOS) was 185–555GBq/μmol.